Multifunctional nanomaterials composed entirely of active pharmaceutical ingredients for synergistically enhanced antitumor and antibacterial effects - An, Qi; Wang, Dongmei; Huang, Liang; Chen, Xiangyu; Wang, Chuan (Frontiers in Pharmacology, 2024)
Introduction Multifunctional nanomaterials are emerging as promising tools for treating both cancer and bacterial infections. However, integrating dual therapeutic capabilities into a single system remains challenging. This study presents multifunctional nanoparticles (ECI-NPs) based on Epigallocatechin gallate (EGCG) oligomers, Curcumin (CUR), and Indocyanine Green (ICG) for combined cancer and bacterial treatment. Methods ECI-NPs were synthesized via oxidative coupling of EGCG, CUR, and ICG. The nanoparticles were characterized for stability, size, drug loading, and release profiles. Cellular uptake, phototoxicity in melanoma cells, and antibacterial activity against Escherichia coli and Staphylococcus aureus were also evaluated. Results ECI-NPs demonstrated optimal stability, high drug loading, and controlled release. Cellular studies showed increased uptake and greater phototoxicity in melanoma cells compared to free drugs. ECI-NPs also exhibited enhanced anticancer effects and strong antibacterial activity, outperforming the individual components. Discussion The polyphenol-based ECI-NPs offer synergistic therapeutic effects, overcoming the limitations of free drugs in terms of solubility and efficacy. This dual-function platform shows potential for broader biomedical applications, addressing challenges in cancer and bacterial infections. Further research will focus on in vivo studies and clinical translation.